Risk Factors of Dyslexia in Pre-school Children - Tūbele, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article is devoted to actualize early risk factors of dyslexia in pre-school children.There are a lot of research about dyslexia and its impact on the child/pupil's development, learning and other areas of life. Part of the research concerns the development of a child in pre-school age determining, what factors influence acquisition of reading skills and predict potential difficulties. The article is devoted to reveal early risk factors of specific reading disorder (dyslexia), touches diagnostic possibilities and states what is the role of early intervention in the development of a child. Risk factor groups are described previously, but still the practical activities are far behind the need. Risk factor groups are analyzed in this article as well as necessity for early intervention.